1975
DOI: 10.3758/bf03333233
|View full text |Cite
|
Sign up to set email alerts
|

Choice and self-control in children: A test of Rachlin’s model

Abstract: Rachlin and Green (1972) proposed a model which analyzed self control as a reversal of preference for two reward values in time_ The present study investigated the utility of the model in the investigation of self-control in children. Two boys (ages 9-10) were exposed to a chain of events in which a left alternative (initial link) lead to a choice (terminal link) between a small, immediate reward (2 tokens) or a lar!!e. de laved reward (4 tokens delaved 4 sec). Equal preference was found for both left and ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
11
0

Year Published

1979
1979
2000
2000

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 3 publications
2
11
0
Order By: Relevance
“…The findings in this study are consistent with those found in investigations using pigeons and children as subjects in delay and self-control studies (Burns & Powers, 1975;Logue & Mazur, 1981;Logue, Rodriguez, Peina-Correal, & Mauro, 1984; studies (e.g., Ferster, 1953;. The choice of the larger reinforcer during the postassessment at delays presented beyond those during training must also be examined under the matching law and delay-reduction hypothesis.…”
Section: Trials To Criterion During Trainingsupporting
confidence: 80%
See 1 more Smart Citation
“…The findings in this study are consistent with those found in investigations using pigeons and children as subjects in delay and self-control studies (Burns & Powers, 1975;Logue & Mazur, 1981;Logue, Rodriguez, Peina-Correal, & Mauro, 1984; studies (e.g., Ferster, 1953;. The choice of the larger reinforcer during the postassessment at delays presented beyond those during training must also be examined under the matching law and delay-reduction hypothesis.…”
Section: Trials To Criterion During Trainingsupporting
confidence: 80%
“…The matching law predicts a reversal in choice from the larger, more delayed reinforcer to the smaller, less delayed one as delays to both reinforcers decrease (Ainslie & Herrnstein, 1981;Green et al, 1981). Previous research has illustrated this phenomenon by showing that children and pigeons tend to select smaller, less delayed reinforcers, even when offered the alternative of larger reinforcers that are available only after a delay (Ainslie, 1974;Ainslie & Herrnstein, 1981;Burns & Powers, 1975;Green et al, 1981;Green & Snyderman, 1980). …”
mentioning
confidence: 99%
“…Further, the few laboratory experiments that have reported consistent impulsive behavior in humans have either used children (Burns & Powers, 1975) or have used negative reinforcement with adults (Navarick, 1982;Solnick, Kannenberg, Eckerman, & Waller, 1980). Both of these studies with adults used escape from loud noise as the reinforcer, and both obtained basic confirmation of the matching law when data were averaged over large groups of subjects.…”
mentioning
confidence: 91%
“…However, experimentally naive adult hu- man subjects choosing between different amounts of reinforcement have shown discrepancies from matching (Bangert, Green, Snyderman, & Turow, 1985;Schmitt, 1974;Wurster & Griffiths, 1979). Further, the few laboratory experiments that have reported consistent impulsive behavior in humans have either used children (Burns & Powers, 1975) or have used negative reinforcement with adults (Navarick, 1982;Solnick, Kannenberg, Eckerman, & Waller, 1980). Both of these studies with adults used escape from loud noise as the reinforcer, and both obtained basic confirmation of the matching law when data were averaged over large groups of subjects.…”
mentioning
confidence: 99%
“…This approach resembles others used in the laboratory to establish self-control choice by gradually increasing the delay to the large reinforcer in children identified as impulsive (Schweitzer & Sulzer-Azaroff, 1988) and in individuals with mental retardation in both laboratory (Ragotzy et al, 1988) and applied (Dixon et al, 1998) settings. However, few studies of self-control with humans with limited development have used tokens (but see Burns & Osborne, 1975); instead, terminal reinforcers (e.g., stickers, snacks, time socializing) were delivered either immediately or after a delay. An obvious advantage of the systematic use of tokens with such individuals includes the possibility that longer delays in reinforcement may be possible without degrading self-control, in part because of the variety of reinforcers that can be delivered during the token-exchange period.…”
Section: Basic Research Related To Delayed Reinforcementmentioning
confidence: 99%